Pengembangan Sistem Keamanan untuk E-Commerce - Saputra, I Gusti Ngurah Indra; Sasmita, Gusti Made Arya; Wiranatha, Anak Agung Ketut Agung Cahyawan (Jurnal Ilmiah Merpati (Menara Penelitian Akademika Teknologi Informasi); Vol. 5, No. 1 April 2017, 2017)
E-commerce is a remote goods or services transaction activity between two company (business to business) or between company with customers (business to consumer). Ecommerce was simplifying the transaction process between producers and consumers, butthere is a risk of security issue if doing transactions on e-commerce. A common e-commercesecurity system using another protocol security e.g. SSL (Secure Socket Layer) so these ecommerce security system is very dependent with these security protocol. The e-commercesecurity problem was fixed by developed security system that using security system directly onthe web page. The system is designed to securing transaction data using RC6 encryption, RC6encryption key is secured by RSA encryption, and encrypted data is encoded by Base64. Theresulting security system is blocking transaction data when users clicking submit transactionbutton, then these transaction data encrypted using applied algorithm before send it into serverso transaction data was secured without aid of another security protocol e.g. SSL (SecureSocket Layer).